Learning at Home During the Covid-19 Pandemic by Optimizing Video Based Tutorials - Sholeh, Muhammad; Suraya, Suraya; Andayani, Dina (Universitas Nusantara PGRI Kediri, 2021)
The learning process carried out at home during the COVID-19 pandemic demands the creativity of educators so that the material provided can be understood by students. The problems that arise during online lectures are changing the habits of students who always get detailed explanations from lecturers, while in online lectures the interaction between students and lecturers is limited and there are student guidelines for independent study. The research was conducted with the aim of evaluating the learning process at home using video-based tutorials. The methodology is carried out using the ADIIE model. The process of making tutorials is done by making a video story board that will be made and implementing the story board using Camtasia Studio. The results of the study resulted in Structured Programming course material in the form of video tutorials from meetings 1 to 10. The evaluation results showed that 39.1% of students answered very well to the question of whether videos can be used for self-study at home and 60.8% answered quite well.